Epidemiology of basal cell carcinoma: a 10-year comparative study. Issue 2 (February 2018) - Devine, C.; Srinivasan, B.; Sayan, A.; Ilankovan, V.
Abstract: Basal cell carcinoma (BCC) is a slow-growing and locally aggressive skin cancer. Despite its high incidence, good quality epidemiological data are sparse. We therefore organised a retrospective study of two separate years' incidence of BCC in one county within the United Kingdom (Dorset) with an interval of 10 years between them. There were 2455 patients in 2006, and 3797 in 2016, who had a new diagnosis with corresponding crude incidences of 459.99 and 491.92/100, 000 person-years. The male:female ratio was 1:071 for both years. The head and neck was the most common site, with the cheek, nose, and forehead being the most common subsites. This is a substantial increase in the incidence of BCC, and is much higher than previous reported rates for the UK. More stringent local and national registries are required to monitor the increasing numbers of BCC and help health care systems to plan preventive strategies and provide the most effective treatment.